Social health protection in Cambodia: Challenges of policy design and implementation. (29th April 2019) - Kwon, Soonman; Keo, Lundy
Abstract: The Government of Cambodia is implementing ambitious reform initiatives to improve the country's social health protection system. In January 2018, it was announced that the Health Equity Fund (HEF), which is fully subsidized by a joint government‐donor initiative for the reimbursement of user fees for the poor at public health facilities, is to be expanded to some segments of informal workers belonging to associations, as well as to commune and village chiefs. Since 2017, the National Social Security Fund (NSSF) has provided social health insurance for formal economy workers in enterprises with eight employees or more. In January 2018, it was expanded to civil servants and all employees regardless of the size of the enterprise. However, this article highlights that the new ambitious reforms are not accompanied by careful planning as regards funding, service delivery, human resources and institutional design. This article therefore aims to examine key policy issues and challenges for Cambodia's ambitious reform of its social health protection system in terms of resource generation, population coverage, strategic purchasing and governance.